MORDOVIAN STATE PEDAGOGICAL INSTITUTE NAMED AFTER M.E. EVSEVIEV AS A TRAINING CENTER FOR TEACHING STAFF IN THE REGION - Vastly V. Kadakin (Высшее образование в России)
This paper examines the main directions of modernization of the scientific and educational process and social infrastructure of the Mordovian State Pedagogical Institute named after M. E. Evseviev as one of the centers of social and economic development of the region, as a career lab for preparation teaching staff for varied activities in the spheres of education, culture, physical culture and sport in the region.